Public Speaking, Leadership, Organization Dan Bullying Di SMP PGRI 06 Gandrungmangu Desa Karanggintung Tahun 2023 - Syahida Cahya Allistya; Achmad Zakaria; Wigiyanto Wigiyanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Public Speaking, Leadership, Organization and Bullying Prevention training was held with the hope of raising awareness of the importance of public speaking skills, organizational enthusiasm and the importance of leadership for students, as well as the negative impact of bullying in the school environment. This training will later be carried out at SMP PGRI 06 Gandrungmangu with the hope that students will be able to improve their speaking skills in front, be able to build a good organization and improve their leadership skills and minimize bullying in the classroom.